2019
DOI: 10.1128/jvi.01223-19
|View full text |Cite
|
Sign up to set email alerts
|

HA-Dependent Tropism of H5N1 and H7N9 Influenza Viruses to Human Endothelial Cells Is Determined by Reduced Stability of the HA, Which Allows the Virus To Cope with Inefficient Endosomal Acidification and Constitutively Expressed IFITM3

Abstract: Previous studies revealed that certain avian influenza A viruses (IAVs), including zoonotic H5N1 and H7N9 IAVs, infect cultured human lung microvascular endothelial cells (HULEC) more efficiently than other IAVs and that tropism to HULEC is determined by viral hemagglutinin (HA). To characterize mechanisms of HA-mediated endotheliotropism, we used 2:6 recombinant IAVs harboring HAs from distinctive avian and human viruses and found that efficient infection of HULEC correlated with low conformational stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…In addition, our work provided new insights into the antiviral mechanism of IFITM1 related to inhibiting organelles acidification. The previous research also showed that the endosomes in HULEC cells with a high basal level of IFITM3 were less acidic than in MDCKs [35]. The mechanism may be applicable to explain how IFITM1 restricts other viruses entering cells by clathrin-mediated endocytosis.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, our work provided new insights into the antiviral mechanism of IFITM1 related to inhibiting organelles acidification. The previous research also showed that the endosomes in HULEC cells with a high basal level of IFITM3 were less acidic than in MDCKs [35]. The mechanism may be applicable to explain how IFITM1 restricts other viruses entering cells by clathrin-mediated endocytosis.…”
Section: Discussionmentioning
confidence: 84%
“…Embryonic fibroblasts (MEFs) from ifitmDel -/mice are more sensitive to IAV than MEFs from wild-type mice, and the anti-IAV effect of type I and II IFN is weakened in ifitmDel -/mice (26). Moreover, the infection of pseudo-retroviruses with different hemagglutinin proteins (H1, H3, H5, and H7) as outer membranes can be effectively inhibited by IFITM1, 2, and 3 (7,24,(27)(28)(29). Studies have shown that arboviruses, including DENV and WNV, have similar sensitivity to IFITM-mediated restriction (30).…”
Section: The Antiviral Spectrum Of Ifitmsmentioning
confidence: 99%
“…Influenzavirus HA belongs to the category of fusion proteins triggered by exposure to low pH alone. Interestingly, human lung microvascular endothelial cells show less efficient endosomal acidification than human epithelial cells ( 159 ), and this renders endothelial cells less permissive to infection by seasonal influenzavirus and LPAIV strains. In addition, endothelial cells express high constitutive levels of antiviral interferon-induced transmembrane protein (IFITM) 3 in endosomal and lysosomal compartments.…”
Section: Specific Factors That Determine the Ability To Infect Endothmentioning
confidence: 99%
“…This protein arrests endosomal fusion of seasonal human influenzavirus in endothelial cells at the hemifusion stage ( 160 ). Overcoming these obstacles, HPAIV strains have a less stable conformation of the HA molecule that allows fusion to take place at a higher pH ( 159 ) and allows infection in early endosomal compartments. The ability to efficiently fuse at a higher pH probably also mediates the relative resistance of HPAIV to the antiviral action of IFITM3 ( 161 ).…”
Section: Specific Factors That Determine the Ability To Infect Endothmentioning
confidence: 99%